Analisis Perilaku Konsumen pada Pengambilan Keputusan Pembelian di Pasar Tradisional Kota Surakarta - Ali Arif Setiawan; Christina Nur Wijayanti; Wahjoe Mawardiningsih; Jeratallah Aram Dani (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze consumer behavior in purchasing decision-making at traditional markets in Surakarta City. The focus of this research is to identify the factors that influence consumer purchasing decisions, such as price, product quality, location, service, and shopping habits. The method used is a quantitative approach with a survey method. Data were collected through the distribution of questionnaires to 100 respondents who are active consumers at several traditional markets in Surakarta, such as Pasar Gede, Pasar Klewer, and Pasar Legi. The data analysis technique used is multiple linear regression to examine the influence of independent variables on the dependent variable. The results show that price, product quality, and service have a significant influence on purchasing decisions, while location and shopping habits do not show a significant influence. These findings indicate that consumers in traditional markets in Surakarta tend to prioritize economic value and service interaction in their purchasing decisions. This research is expected to provide input for traditional market managers in improving competitiveness amidst the growth of modern markets.